Correlation of Short Chain Fatty Acid (SCFA) Levels with Transient Elastography Values and Controlled Attenuation Parameters in Patients with Non-Alcoholic Fatty Liver Disease (NAFLD) - Desi Astari; Chyntia Olivia Maurine Jasirwan; Cosmas Rinaldi Adithya Lesmana; Marcellus Simadibrata; Juferdy Kurniawan; Evy Yunihastuti; Kuntjoro Harimurti; Pringgodigdo Nugroho (Acta Medica Indonesiana)
Background: The current hypothesis regarding the mechanism of Non-Alcoholic Fatty Liver Disease (NAFLD) is the multiple hit theory, where one of the factors involved is gut microbiota. Short-chain fatty acid (SCFA) is the main metabolite of gut microbiota and is suspected to play a role in the development of NAFLD. This study aims to determine the correlation between SCFA levels (acetate, propionate, butyrate) and the degree of fibrosis and steatosis in patients with NAFLD assessed by controlled attenuation parameter (CAP) and transient elastography (TE). Methods: A cross-sectional study that included 33 consecutively selected patients at Cipto Mangunkusumo Hospital was conducted from January to August 2023. Fecal sample collection was performed for SCFA examination using GC-MS (Gas Chromatography-Mass Spectrometry). Absolute fecal SCFAs were analyzed for correlation with steatosis and fibrosis based on controlled attenuation parameter (CAP) and transient elastography (TE) values. Results: Subjects were predominantly female (51.5%), with an average age of 49 years, an average CAP value of 296 dB/m, and a median transient elastography value of 6.1 kPa. The ratio of acetate, propionate, and butyrate values in the subjects was 59:24:17. A moderate negative correlation was observed between the absolute butyrate and CAP values (r=-0.522; p=0.002). Conclusion: There is no correlation was identified between short-chain fatty acid levels and transient elastography values.